2022
DOI: 10.1371/journal.pone.0269138
|View full text |Cite
|
Sign up to set email alerts
|

Severity of infection with the SARS-CoV-2 B.1.1.7 lineage among hospitalized COVID-19 patients in Belgium

Abstract: Introduction The pathogenesis of COVID-19 depends on the interplay between host characteristics, viral characteristics and contextual factors. Here, we compare COVID-19 disease severity between hospitalized patients in Belgium infected with the SARS-CoV-2 variant B.1.1.7 and those infected with previously circulating strains. Methods The study is conducted within a causal framework to study the severity of SARS-CoV-2 variants by merging surveillance registries in Belgium. Infection with SARS-CoV-2 B.1.1.7 (‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Van Goethem et al [ 30 ] compared COVID-19 disease severity between hospitalized patients in Belgium infected with the SARS-CoV-2 variant B.1.1.7 (Alpha) and those infected with previously circulating strains. Employing a causal framework, the authors observed no difference between patients infected with B.1.1.7 and those infected with older strains in terms of disease severity or in-hospital mortality.…”
Section: Studies Resulting From the Genomic Surveillance Initiativementioning
confidence: 99%
See 2 more Smart Citations
“…Van Goethem et al [ 30 ] compared COVID-19 disease severity between hospitalized patients in Belgium infected with the SARS-CoV-2 variant B.1.1.7 (Alpha) and those infected with previously circulating strains. Employing a causal framework, the authors observed no difference between patients infected with B.1.1.7 and those infected with older strains in terms of disease severity or in-hospital mortality.…”
Section: Studies Resulting From the Genomic Surveillance Initiativementioning
confidence: 99%
“…Employing a causal framework, the authors observed no difference between patients infected with B.1.1.7 and those infected with older strains in terms of disease severity or in-hospital mortality. However, Van Goethem et al [ 30 ] found that the estimated standardized risk of being admitted to an ICU was significantly higher when infected with the B.1.1.7 variant, and that among the younger age group (≤65 years), B.1.1.7 was significantly associated with both severe COVID-19 progression and ICU admission.…”
Section: Studies Resulting From the Genomic Surveillance Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…This sensitivity is especially important for the detection of emerging variants before they reach 1% of the circulating strains as was observed for the B.1.617.2 variant 2,24,41 . Also, the data gathered from the baseline genomic surveillance allowed the Belgian Sequencing Consortium to conduct or participate to several active surveillance studies concerning phylogenetic analyses, VOC‐associated disease severity assessments and outbreak investigations such as in nursing homes and others 26,49–54 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hospital and ICU loads increase in epidemiological wave periods, with increased loads associated with increased disease severity and higher in-hospital mortality [107][108][109][110] of COVID-19 patients. Ideally, analyses should be adjusted for hospital load [111], ICU load [10,112] and COVID-19 incidence [111,113] to eliminate spurious association through these factors.…”
Section: Pressure On the Healthcare Systemmentioning
confidence: 99%